Performance Evaluation of Fiber-Reinforced, Stress Relief Asphalt Layers to Suppress Reflective Cracks - Cheolmin Baek (Applied Sciences, 2020)
In this study, the performance of the fiber-reinforced, stress-absorbing membrane interlayer (F-SAMI) method was evaluated to suppress reflective cracks, which usually occur when the overlay method is applied for the maintenance of existing aged pavement. The F-SAMI method has an effect of suppressing the occurrence of reflective cracks by constructing a material composed of emulsified asphalt, fibers, and aggregates between the surface layer and the base layer. The mechanical performance of the F-SAMI was evaluated through both small-scale (model mobile load simulator 3, or MMLS3) and large-scale (accelerated pavement testing, or APT) pavement acceleration tests on the specimen and pavement structures, respectively, with the F-SAMI layer applied between the surface layer and the base layer. In this study, the base layer was made with an asphalt mixture or a concrete mixture, and the surface layer was made with polymer-modified stone mastic asphalt (PSMA). Evaluation was conducted by applying four types of F-SAMI layer, according to the content of asphalt and aggregate and compared with the case where general tack coating was applied. In order to induce the occurrence of reflective cracks, a notch was made in the center of the base layer. As a result of the experiment, it was shown that regardless of the mixture type of the base layer, the specimen or pavement with the F-SAMI method was much more resistant to reflective cracking than those with the tack coating. In addition, it was found that the F-SAMI method with aggregates was more resistant to reflective cracks than that without aggregates.